Zirconium oxo clusters as discrete molecular catalysts for the direct amide bond formation. Issue 10 (5th April 2022) - Zhang, Yujie; de Azambuja, Francisco; Parac-Vogt, Tatjana N.
Abstract : A discrete dodecanuclear Zr oxo cluster catalyzed the direct formation of amide bonds without the need of water scavenging or dry reactions conditions showcasing the potential of these molecular clusters to become a new class of efficient catalysts. Abstract : Zirconium compounds are prime catalysts in organic synthesis; however, their utility is often diminished by their moisture sensitivity. Here, we investigate zirconium oxo cluster (ZrOC) [Zr6 (OH)4 O4 (OAcr)12 ]2 (OAcr = acrylate) (Zr 12 ), as an air and moisture stable molecular catalyst for the atom economic formation of amide bonds directly from non-activated carboxylic acids and amines. The Zr 12 is readily prepared in one step from commercially available zirconium salts and carboxylic acids, and unlike the majority of metal complexes developed so far, it catalyzes the intermolecular formation of various amides in high yields without requiring water scavenging, inert or anhydrous reactions conditions, or any additives. Detailed mechanistic evaluation through control and NMR experiments suggests that the Zr 12 cluster, rather than a lower nuclearity species, is the catalytic active species involved in the reaction. Further, a comparison of Zr 12 performance with previously reported ZrCl4 under the same conditions showcases several advantages of Zr 12 over conventional catalysts, underlining the potential of ZrOC as a new class of practical, readily available, and stable catalysts.